The concept of "hiya" and how it is manifested in language and behavior - Saludades, Agripina Casilang 1946-
The study concentrates on the different aspects of "hiya", its sources and manifestations as revealed in the stories of our local magazines as well as observed by the writer herself. It attempts to explain the functions of "hiya" as a value in Philippine society. The study consists of three main parts: "hiya" manifested in language, "hiya" manifested in behavior, and "hiya" manifested in language and behavior.